Modern Communication Technologies in Notification of Notarial Actions in Russia - INSHAKOVA, Olegovna Agnessa; GONCHAROV, Ivanovich Alexander; SMIRENSKAYA, Vitaliyevna Elena; DOLINSKAYA, Vladimirovna , Vladimira (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017, 2017)
In the article studies modern communication technologies used in the Russian Federation for notarial acts. The main provisions of the issues for the development of modern information and telecommunication technologies for organizing notarial activities, within the framework of which the main stages of system construction, intermediate and final results, its targets, tasks, organizational structure and functions are determined. As a basis for providing all types of information interaction, the article presents the Unified Information System of the Notariat of Russia. The authors studying the novelties of the legislation on the application of information and telecommunication technologies for notarial acts, the peculiarities of electronic interaction with the state authorities of the Russian Federation. The conclusion is confirmed, that the Russian notary is ready to work in the new conditions, is focused on those requirements that dictate the modern information space.